Variação temporal da comunidade de formigas ao longo de um gradiente altitudinal - Rayana Mello Souza (2016)
The need to study and understand how climate change will affect biodiversity over time is increasingly. Altitudinal gradients are great ecological models, within which the decreased richness with increasing altitude is the pattern most encountered. The mechanisms inherent in this pattern are generally associated with changes in conditions such as climate and soil, insofar as we climbed the mountain, and can act in different spatial scales (spatial and temporal). Being thermophilic beings, the ants can be influenced by temperature, both in the local and global scale. Partitioning of diversity is a useful way to deal with these mechanisms that act at different scales, in this way, the objective of this study was to test whether the climatic factors (temperature, humidity and precipitation) determine the temporal variation of ants in different scales (, e ) in a tropical altitudinal gradient and if this effect changes with elevation. The study was conducted in Serra do Cipó using seven areas in different altitudinal quotas (800m to 1400m). Fifteen points were sampled per area, where was installed "pitfall" traps from January/2012 to January/2014, quarterly. Multiplicative approach was used to calculate the components of (gamma) , (Alpha) and (beta) diversities, which were represented at each collection by the richness of each altitude, average wealth of each altitude and the ratio of these parameters ( = /), respectively, being the last a representation of the diversity of differentiation in each. A hundred and sixty six (166) species of ants were sampled. Over time, changes happened in the activity of ants across the gradient, observing a positive effect of temperature in the local diversity and humidity in the regional diversity, but the effects did not differ with height. None of the climatic factors determined the temporal variation of (beta) diversity along the studied gradient. Our data showed that the climate variation has a strong relationship with the community temporal variation of ants and corroborate the hypothesis of changes at different levels of ecological structure in mountains ecosystems, as predicted by the models of global warming.